Boosting the circularly polarized luminescence of pyrene-tiaraed pillararenes through mechanically locking - Jing-Lin Song; Chao Chen; Xue Li; Yefei Jiang; Zhiyong Peng; Xu-Qing Wang; Hai-Bo Yang; Wei Wang (Nature Communications)
Abstract Attributed to their unique dynamic planar chirality, pillar[n]arenes, particularly pillar[5]arenes, have evolved as promising platforms for diverse applications such as circularly polarized luminescence (CPL) emitters. However, due to the unit flipping and swing, the achievement of excellent CPL performances of pillar[5]arenes in solution state remains a formidable challenge. To deal with this key issue, a mechanically locking approach has been successfully developed, leading to boosted dissymmetry factor (g lum) values of pyrene-tiaraed pillar[5]arenes up to 0.015 through the formation of corresponding [2]rotaxanes. More importantly, taking advantage of the stably locked co-conformers, these resultant [2]rotaxanes maintain excellent CPL performances in diverse solvents and wide range of concentrations, making them promising candidates for practical applications. According to this proof-of-concept study, we have not only successfully developed a powerful strategy for the rational design of chiral luminescent materials with desired CPL performances but also contributed a promising platform for the construction of smart chiral materials.